Legal Regulations Against Violence in Marriage - Febriansyah, Ferry Irawan; Agiyanto, Ucuk; Ikhwan, Afiful; Utami, Nurul Tri (International Journal of Law and Society, 2024)
This study aims to analyze the legal provisions on marital violence with a focus on the implementation of the Law on the Protection of Women and Children. The problem analysis highlights the shortcomings in the implementation of the law that result in a lack of protection for victims of domestic violence. In addition, the challenges in law enforcement against perpetrators of marital violence are also discussed. The research method used is the normative legal research method, which analyzes various laws and regulations, official documents, and related court decisions. The analysis results show that although there is already a law that regulates the protection of women and children, namely the PPA Law. In the implementation of the PPA Law, there are efforts made to protect women and children from marital violence. These steps include case identification, handling reports, investigation processes, prosecution of perpetrators of violence, and protection and rehabilitation for victims. Further efforts are needed to strengthen law enforcement and increase public awareness of the rights of women and children in the context of marriage.